SEX‐SPECIFIC PATTERNS OF MORPHOLOGICAL DIVERSIFICATION: EVOLUTION OF REACTION NORMS AND STATIC ALLOMETRIES IN NERIID FLIES. (1st February 2014) - Cassidy, Elizabeth J.; Bath, Eleanor; Chenoweth, Stephen F.; Bonduriansky, Russell
Abstract: The consequences of sex‐specific selection for patterns of diversification remain poorly known. Because male secondary sexual traits are typically costly to express, and both costs and benefits are likely to depend on ambient environment and individual condition, such traits may be expected to diversify via changes in reaction norms as well as the scaling of trait size with body size (static allometry). We investigated morphological diversification within two species of Australian neriid flies ( Telostylinus angusticollis, Telostylinus lineolatus ) by rearing larvae from several populations on larval diets varying sixfold in nutrient concentration. Mean body size varied among populations of T. angusticollis, but body size reaction norms did not vary within either species. However, we detected diversification of reaction norms for body shape in males and females within both species. Moreover, unlike females, males also diversified in static allometry slope and reaction norms for static allometry slope of sexual and nonsexual traits. Our findings reveal qualitative sex differences in patterns of morphological diversification, whereby shape–size relationships diversify extensively in males, but remain conserved in females despite extensive evolution of trait means. Our results highlight the importance of incorporating plasticity and allometry in studies of adaptation and diversification.